2021
DOI: 10.14806/ej.26.1.981
|View full text |Cite
|
Sign up to set email alerts
|

Stress among pediatric oncology staff. A systematic review

Abstract: Cancer is considered one of the dominant life-threatening diseases in children. Working in the field of pediatric oncology, although rewarding, can be a source of stress and emotional burden for health care providers. The aim of this systematic review was to summarise the evidence regarding the occupational stress of health care providers working with pediatric cancer patients. Extensive search of the Pubmed and Scopus databases was performed to identify studies relevant to the topic. Initial search retrieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
2
0
1
Order By: Relevance
“…27 A systematic review was done to capture and categorize pediatric oncology staffs’ stress and revealed two domains of stressor—(a) organizational issues such as workload, limited time, lack of communication with colleagues, and lack of supplies and staffing; and (b) interaction between staffs and patient or families such as communications on care trajectories with conflicted points of view, witnessing pain and patient loss, etc. 26 Although similar results have been seen, this study could report more detailed and variety of situations which pediatric nurses experience as many of the previous studies have used such instruments to examine the nurses’ moral distress level, which have limitations of discovering detailed situations that are not listed in the instruments. As the need for pediatric-appropriate instruments has been reported in previous studies, this study’s results will provide fundamental knowledge to future studies related to instrument development.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…27 A systematic review was done to capture and categorize pediatric oncology staffs’ stress and revealed two domains of stressor—(a) organizational issues such as workload, limited time, lack of communication with colleagues, and lack of supplies and staffing; and (b) interaction between staffs and patient or families such as communications on care trajectories with conflicted points of view, witnessing pain and patient loss, etc. 26 Although similar results have been seen, this study could report more detailed and variety of situations which pediatric nurses experience as many of the previous studies have used such instruments to examine the nurses’ moral distress level, which have limitations of discovering detailed situations that are not listed in the instruments. As the need for pediatric-appropriate instruments has been reported in previous studies, this study’s results will provide fundamental knowledge to future studies related to instrument development.…”
Section: Discussionsupporting
confidence: 56%
“…Some situations were similar to those found in previous studies conducted on pediatric nurses. 25,26 One study that was conducted in pediatric oncology settings in Sweden used an instrument to measure the level of moral distress and highlighted that nurses experienced morally distressing situations more frequently than medical doctors and nursing assistants. 25 The study identified lack of competence and continuity of care and inadequate staffing of nurses as contributing factors to morally distressing situations.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a literature review, several studies have shown that pediatric oncology nurses are exposed to high stress. Some studies point to differences between nurses and doctors [34]. To our knowledge, studies directly comparing the pediatric palliative care experiences of doctors and nurses working in pediatric oncology departments are limited, and could be an essential focus in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Uma interação íntima entre crianças, pais e equipe de oncologia pediátrica geralmente é desenvolvida como parte do processo de hospitalização e, desse modo, é praticamente inevitável não se envolver emocionalmente com o que ocorre nesse contexto. Trabalhar na área da oncologia pediátrica e prestar assistência psicológica e médica em ambiente hospitalar pode ser uma experiência gratificante, contudo pode ser simultaneamente uma fonte de estresse e sobrecarga emocional para os profissionais de saúde (Zarenti et al, 2021).…”
Section: Discussionunclassified